Study on the synthesis of amide compound by arylboronic acid-catalyzation - Yujing WEI; Yihua YANG; Kaili YONG; Qian LU; Shouxin LIU (Journal of Hebei University of Science and Technology, 2018)
Amide bond is a special structure that can exhibit high physiological activity. The most ideal way to form amide is the direct reaction between carboxylic acid and amine, but this reaction has to be under strong heat condition. A method is proposed for direct synthesis of amides by direct condensation of fatty acids and primary amines under milder conditions, namely catalyzed by simple arylboronic acids. The reaction system is established by direct amidation of phenylacetic acid and benzylamine. The type, amount of catalyst, reaction solvent, reaction time, and reaction temperature are optimized. The result shows that with fluorobenzene as solvent and phenylboronic acid as catalyst, organic acids are firstly treated for 1 h at reflux temperature, then the reaction continues for 12 h after adding fatty amines, and under the optimum reaction condition, the yield of the corresponding amide is above 80%. The product is characterized by 1H NMR and 13C NMR. The method is a new simple effective method for preparing amide compounds and the product is easy to purify.